If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + 4)(5n + -6) = 0 Reorder the terms: (4 + n)(5n + -6) = 0 Reorder the terms: (4 + n)(-6 + 5n) = 0 Multiply (4 + n) * (-6 + 5n) (4(-6 + 5n) + n(-6 + 5n)) = 0 ((-6 * 4 + 5n * 4) + n(-6 + 5n)) = 0 ((-24 + 20n) + n(-6 + 5n)) = 0 (-24 + 20n + (-6 * n + 5n * n)) = 0 (-24 + 20n + (-6n + 5n2)) = 0 Combine like terms: 20n + -6n = 14n (-24 + 14n + 5n2) = 0 Solving -24 + 14n + 5n2 = 0 Solving for variable 'n'. Factor a trinomial. (-4 + -1n)(6 + -5n) = 0Subproblem 1
Set the factor '(-4 + -1n)' equal to zero and attempt to solve: Simplifying -4 + -1n = 0 Solving -4 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1n = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1n = 0 + 4 -1n = 0 + 4 Combine like terms: 0 + 4 = 4 -1n = 4 Divide each side by '-1'. n = -4 Simplifying n = -4Subproblem 2
Set the factor '(6 + -5n)' equal to zero and attempt to solve: Simplifying 6 + -5n = 0 Solving 6 + -5n = 0 Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -5n = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -5n = 0 + -6 -5n = 0 + -6 Combine like terms: 0 + -6 = -6 -5n = -6 Divide each side by '-5'. n = 1.2 Simplifying n = 1.2Solution
n = {-4, 1.2}
| 4.5=y+2.8 | | 44=8(w+2)+4 | | 25-8x=89 | | .04x+.30(24-x)=3.6 | | 248x+744=1240 | | 54x+216=648 | | 9(t+40)+4=49 | | 2sinx-cosx= | | 23x+92=207 | | x+6(3x-2)=7 | | x+7p= | | y^2+2y=x-3 | | -2s-11+-4s=-41 | | 16(s-5)=4 | | 6=0.2d | | 3x-3x=-20+6 | | 4(s-5)=16 | | 15=14h+1 | | 5x(2+3)=90 | | 3(x-5)+1=x+2 | | L=1/2(p-2W) | | 64+10x=214 | | 2=-3a+5 | | 10x+4x+4+7=11x+3+2x | | 5p+4(1-3p)= | | 17/2x:1 | | 80.8=8(m+2.9) | | ln(2x)+ln(3x)=ln(4x) | | 7x-3=6(x+20) | | 5x+(-4)=11 | | 2(m-n)=x+7 | | 6m+3m=102 |